1995
DOI: 10.1002/pro.5560040805
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure of the potassium channel inhibitor agitoxin 2: Caliper for probing channel geometry

Abstract: The structure of the potassium channel blocker agitoxin 2 was solved by solution NMR methods. The structure consists of a triple-stranded antiparallel @-sheet and a single helix covering one face of the 0-sheet. The cysteine side chains connecting the &sheet and the helix form the core of the molecule. One edge of the 0-sheet and the adjacent face of the helix form the interface with the Shaker K+ channel. The fold of agitoxin is homologous to the previously determined folds of scorpion venom toxins. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
108
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(112 citation statements)
references
References 40 publications
4
108
0
Order By: Relevance
“…The second part, consisting of residues 13Ϫ32 the Sequelon membrane. Their identities were verified by amino was based on region 19Ϫ38 of agitoxin 2 [58]. This was carried acid analysis and electrospray mass spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The second part, consisting of residues 13Ϫ32 the Sequelon membrane. Their identities were verified by amino was based on region 19Ϫ38 of agitoxin 2 [58]. This was carried acid analysis and electrospray mass spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…This might be due to the hybridisation of the oligo(T) primer used to prime the first strand of cDNA synthesis, to a poly(A) region situated before the polyadenylation short-chain K-toxins [74,91]. All of them present a hydrophobic core as it is a common characteristic of the synthetic toxin analog PO5-NH 2 [57] and of agitoxin 2 [58] as partial templates. Similar to the template for the N-termiof signal peptides [99].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specificity of scorpion toxin for the various potassium channels has been extensively investigated. The results revealed that binding of the peptide is governed by electrostatic interactions between negatively charged residues in the channel and positively charged residues in the peptide (36,37). The surface electrostatic distribution shown in Fig.…”
Section: Fig 5 Bmp09 Has No Effect On Ca 2؉ -Independent But Voltagmentioning
confidence: 91%
“…The 3-D structures of several short toxins such as charybdotoxin (ChTX) [17], iberiotoxin (IbTx) [31], kaliotoxin (KxTx) [32,33] margatoxin (MgTx) [34], maurotoxin [35], agitoxin (AgTx) [36], noxiustoxin (NTX) [37], PiL [10], insectotoxin I5A [22], LQH-8/6 [27] and chlorotoxin [38] have been determined by NMR spectroscopy and X-ray crystallography. A structure model of ButaIT, generated from the Swiss-…”
Section: Structural Analysismentioning
confidence: 99%